Nordic Media Histories of Propaganda and Persuasion - Norén, Fredrik; Stjernholm, Emil; Thomson, C. Claire (Springer Nature, 2023)
This open access edited volume shines new light on the history of propaganda and persuasion during the Nordic welfare epoch. A common analytical framework is developed that highlights transnational and transmedial perspectives rather than national or monomedial histories. The return of propaganda in contemporary debate underlines the need to historically contextualize the role and function of persuasive communication activities in the Nordic region and beyond. Building on an empirically situated approach, the chapters in this volume break new ground by covering a range of themes, from cultural diplomacy and nation branding to media materiality and information infrastructures. In doing so, the book stresses that the Nordic welfare epoch, with its associated epithet the "Nordic Model", was built not only on governance, social security and economic productivity, but also on propaganda and persuasion.